Complications and length of stay after enhanced recovery after surgery compared to conventional care in colorectal cancer patients in Northern Italy - Fabozzi, Massimiliano; Mereu, Federica; Marinelli, Francesco; Bisceglia, Isabella; Zizzo, Maurizio; Morini, Andrea; Morabito, Fortunato; Zanelli, Magda; Neri, Antonino; Pinto, Carmine; Mangone, Lucia (Frontiers in Surgery, 2025)
BackgroundThis study aims to evaluate postoperative complications and length of stay in colorectal cancer patients undergoing ERAS vs. non-ERAS procedures in a population-based cohort in northern Italy.MethodsPatient characteristics (ASA, tumor site, stage, treatment, BMI) were used. Complications, stratified by Clavien-Dindo and length of stay (LOS), were reported. The odds ratio (OR) and 95% confidence interval (CI) were calculated to evaluate the difference between ERAS and non-ERAS patients.ResultsA total of 319 patients were included, divided into the non-ERAS group (113 patients) and the ERAS group (206 patients). Non-ERAS vs. ERAS group showed more complications (16.8% vs. 13.6%; p-value 0.44) and more days of hospitalization (7.3 vs. 4.8; p-value < 0.01), but less re-surgery (3.5% vs. 4.4%; p-value 0.72), new hospitalizations (3.5% vs. 5.8%; p-value 0.37) and death at 30 days (0.9% vs. 1.5%; p-value 0.66). Multivariate analysis revealed an increased risk in patients with ASA 4 [OR 6.6; 95% CI 1.9–22.6] and a modest, non-significant increase risk in the non-ERAS group [OR 1.3; 95% CI 0.7–2.5].ConclusionsERAS procedures appear to be able to allow intervention even in older patients and those with comorbidities, without compromising the results.